1999
DOI: 10.1096/fasebj.13.15.2257
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Id proteins by the ubiquitin‐proteasome pathway

Abstract: Id proteins act as negative regulators of bHLH transcription factors by forming transcriptionally inactive protein complexes. The proposed function of these proteins includes promotion of cell growth and cell cycle progression, induction of apoptosis, and inhibition of cellular differentiation. We investigated the role of the ubiquitin-mediated proteolytic pathway in the degradation of the Id3 protein. We found Id3 to be a short-lived protein and estimated the half-life to be approximately 20 min in 293 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
87
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 36 publications
12
87
0
1
Order By: Relevance
“…Stability of all ID proteins appears to be regulated by the ubiquitin proteasome system (Anand et al, 1997;Bounpheng et al, 1999;Fajerman et al, 2004;Lasorella et al, 2006). Indeed, ID proteins can bind different components of , 1997), and ID1 and ID3 bind to the JAB1 protein, a subunit of the COP9 signalosome (Bounpheng et al, 1999;Berse et al, 2004;Trausch-Azar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stability of all ID proteins appears to be regulated by the ubiquitin proteasome system (Anand et al, 1997;Bounpheng et al, 1999;Fajerman et al, 2004;Lasorella et al, 2006). Indeed, ID proteins can bind different components of , 1997), and ID1 and ID3 bind to the JAB1 protein, a subunit of the COP9 signalosome (Bounpheng et al, 1999;Berse et al, 2004;Trausch-Azar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ID proteins can bind different components of , 1997), and ID1 and ID3 bind to the JAB1 protein, a subunit of the COP9 signalosome (Bounpheng et al, 1999;Berse et al, 2004;Trausch-Azar et al, 2004). Binding of ID3 to the bHLH protein E47 stabilizes ID3 and partly protects it from proteasomal degradation (Bounpheng et al, 1999). S5A harbors an N-terminal von Willebrand domain, and two C-terminal ubiquitin interacting motifs (UIM), which are important for S5A binding to multiubiquitinated proteins (Hofmann and Falquet, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ID-proteins are necessary for G1 to S-phase transition (Christy et al, 1991;Deed et al, 1993;Barone et al, 1994;Hara et al, 1994;Peverali et al, 1994;Biggs et al, 1995), and ID2 and ID3 are phosphorylated during G1 to S-phase transition by cyclin-dependent kinase (CDK) 2 (CDK2)/ cyclin A or CDK2/cyclin E complexes (Deed et al, 1997;Hara et al, 1997). This phosphorylation event may be a trigger for their ubiquitin-mediated proteasomal degradation and/or alter their bHLH protein binding specificities (Bounpheng et al, 1999;Deed et al, 1997). Various functions of the individual ID-proteins have been described to date: inhibition of differentiation by interfering with differentiation-specific bHLH factors (Benezra et al, 1990;Jen et al, 1992;Kreider et al, 1992), interference with non-bHLH transcription factors (Ohtani et al, 2001;Roberts et al, 2001), induction of apoptosis (Florio et al, 1998;Tanaka et al, 1998;Andres-Barquin et al, 1999), cooperation with the pRb pathway (Iavarone et al, 1994;Hara et al, 1996), and extension of life span (Alani et al, 1999;Nickoloff et al, 2000;Tang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of p204 enhanced, whereas low level of p204 by antisense approach reduced, the degradation of Id2 in the course of osteogenesis of C2C12 cells induced by BMP-2 ( Figure 10B). The degradation of Id protein occurs through the ubiquitinproteasome pathway (Bounpheng et al, 1999;Berse et al, 2004). The Western blots in Figure 10C (top) revealed that in C2C12 cells, in which protein synthesis was blocked by CHX first, ectopic Id2-Flag degradation was inhibited by proteasome blocking agent MG132, because the time of detectable Id2-Flag protein changed from 1.0 to 24 h. The degradation of Id2 accelerated by p204 is also blocked by MG132, because the time of detectable Id2-Flag protein changed from 0 to 24 h.…”
mentioning
confidence: 99%